2015
DOI: 10.9775/kvfd.2014.11393
|View full text |Cite
|
Sign up to set email alerts
|

In ovo Bütirik Asit Beslemesinin Hindilerde Yumurtadan Çıkma, Performans ve İnce Barsak Morfolojisi Üzerine Etkileri

Abstract: The aim of present study was to investigate effect of in ovo administration of butyric acid on hatchability, performance, and small intestinal morphology of turkey poults. Fertilized eggs were subjected to injections with butyric acid (10 mg, 20 mg and 30mg dissolved in 0.5 mL of deionized water) on the d 7 of incubation. Hatching traits, Body weight gain (BWG), feed intake, and feed conversion ratio (FCR) were determined during experiment.Small intestinal morphology included villus height (VH), crypt depth (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Butyric acid (10, 20, or 30 mg/egg) injected into the yolk sac on e7 improved hatching weight and increased villus height in the duodenum, jejunum, and ileum at day 21 post-hatch. In addition, the feed conversion ratio was reduced, and body weight was increased at hatch and days 21–42 post-hatch ( 185 ). Earlier studies have shown that β-hydroxy-β-methyl-butyrate (HMB) and arginine have the potential to improve the development of intestinal digestive and absorptive functions.…”
Section: In Ovo Effects In Other Avian Speciesmentioning
confidence: 99%
“…Butyric acid (10, 20, or 30 mg/egg) injected into the yolk sac on e7 improved hatching weight and increased villus height in the duodenum, jejunum, and ileum at day 21 post-hatch. In addition, the feed conversion ratio was reduced, and body weight was increased at hatch and days 21–42 post-hatch ( 185 ). Earlier studies have shown that β-hydroxy-β-methyl-butyrate (HMB) and arginine have the potential to improve the development of intestinal digestive and absorptive functions.…”
Section: In Ovo Effects In Other Avian Speciesmentioning
confidence: 99%